Randy Lopez goes home a novel - Anaya, Rudolfo A. (Norman : University of Oklahoma Press, 2011)
When he was a young man, Randy Lopez left his village in northern New Mexico to seek his fortune. Since then, he has learned some of the secrets of success in the Anglo world and even written a book called Life Among the Gringos. But something has been missing. Now he returns to Agua Bendita to reconnect with his past and to find the wisdom the Anglo world has not provided. In this allegorical account of Randy s final journey, master storyteller Rudolfo Anaya tackles life s big questions with a light touch.
Keywords: Mexican Americans; Spiritual life; New Mexico